INOVASI PEMERINTAH DESA TUMANG KECAMATAN SIAK KABUPATEN SIAK DALAM MENGELOLA SAMPAH TAHUN 2023 - Julisa, Sarah; Susanto, Agus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
The issue of waste management at the village level has become a significant challenge in achieving a clean and sustainable environment. Tumang Village, Siak Subdistrict, Siak Regency, faces an increasing volume of waste due to population growth and low community awareness in sorting and managing household waste. As a solution, the Tumang Village Government initiated an innovation in waste management through the establishment of the Lestari Waste Bank in collaboration with SD Negeri 10 Tumang, the Family Welfare Empowerment (PKK), and the community. This program is an implementation of Siak Regency Regional Regulation Number 11 of 2012 on Waste Management Guidelines and Village Regulation Number 02 of 2021 on Waste Management and Environmental Cleanliness, aiming to raise environmental awareness and provide economic benefits to the community. This study employs a qualitative descriptive method with data collection techniques including interviews, observation, and documentation. Primary data were obtained from the Village Head, Waste Bank administrators, PKK members, teachers, and residents, while secondary data came from official village documents, activity reports, and relevant scientific literature. Data analysis was carried out through data collection, data reduction, data presentation, and drawing conclusions, using Everett M. Rogers’ Diffusion of Innovation Theory as the analytical framework. The results indicate that the waste management innovation in Tumang Village successfully increased community awareness of environmental cleanliness, strengthened mutual cooperation, and provided economic benefits through recycling activities. Although there are still challenges such as limited facilities and consistency of community participation, the program has proven effective in encouraging social behavior change and serves as a good practice example in realizing the “Green Siak” vision toward sustainable environmental governance. Keywords: Village Government Innovation, Waste Management, Waste Bank, Community Participation